TRAF6-Mediated SM22α K21 Ubiquitination Promotes G6PD Activation and NADPH Production, Contributing to GSH Homeostasis and VSMC Survival In Vitro and In Vivo. Issue 8 (25th September 2015) - Dong, Li-Hua; Li, Liang; Song, Yu; Duan, Zhi-Li; Sun, Shao-Guang; Lin, Yan-Ling; Miao, Sui-Bing; Yin, Ya-Juan; Shu, Ya-Nan; Li, Huan; Chen, Peng; Zhao, Li-Li; et al.
<x xml:space="preserve">Abstract</x> Rationale: Vascular smooth muscle cell (VSMC) survival under stressful conditions is integral to promoting vascular repair, but facilitates plaque stability during the development of atherosclerosis. The cytoskeleton-associated smooth muscle (SM) 22α protein is involved in the regulation of VSMC phenotypes, whereas the pentose phosphate pathway plays an essential role in cell proliferation through the production of dihydronicotinamide adenine dinucleotide phosphate. Objective: To identify the relationship between dihydronicotinamide adenine dinucleotide phosphate production and SM22α activity in the development and progression of vascular diseases. Methods and Results: We showed that the expression and activity of glucose-6-phosphate dehydrogenase (G6PD) are promoted in platelet-derived growth factor (PDGF)-BB–induced proliferative VSMCs. PDGF–BB induced G6PD membrane translocation and activation in an SM22α K21 ubiquitination–dependent manner. Specifically, the ubiquitinated SM22α interacted with G6PD and mediated G6PD membrane translocation. Furthermore, we found that tumor necrosis factor receptor–associated factor (TRAF) 6 mediated SM22α K21 ubiquitination in a K63-linked manner on PDGF-BB stimulation. Knockdown of TRAF6 decreased the membrane translocation and activity of G6PD, in parallel with reduced SM22α K21 ubiquitination. Elevated levels of activated G6PD consequent to PDGF-BB induction led to increased dihydronicotinamide adenine dinucleotide phosphate generation through stimulation of the pentose phosphate pathway, which enhanced VSMC viability and reduced apoptosis in vivo and in vitro via glutathione homeostasis. Conclusions: We provide evidence that TRAF6-induced SM22α ubiquitination maintains VSMC survival through increased G6PD activity and dihydronicotinamide adenine dinucleotide phosphate production. The TRAF6–SM22α–G6PD pathway is a novel mechanism underlying the association between glucose metabolism and VSMC survival, which is beneficial for vascular repair after injury but facilitates atherosclerotic plaque stability.